I-Monsun : future model of sustainable entrepreneurship ecosphere in creative economy - Nik Zulkarnaen Khidzir; Abu Hassan Hasbullah; Khairul Azhar Mat Daud; Ahmad Rasdan Ismail; Suriatini Ismail (Universiti Malaysia Kelantan, 2014)
Creative economy become focus agenda in 21st century around the world to create more business opportunities and prosperity in the job market in the industry. Faculty Creative Technology and Heritage started their another initiative one step further to introduce I-Monsun, it’s private wing to catalyse creative economy development in the country through future model of Sustainable Entrepreneurship Ecosphere (FTKW-SEE). The initiative is our strategic plan to encourage FTKW graduates to become knowledgeable and skilful entrepreneurs, able to meet the demands of the job market and contribute in shaping the creative economy. This sustainable model proposed a complete cycle of income generator and entrepreneurship platform through two major integrated entities (Monsun Industries and Monson Academy) to form the entire complete ecosphere models (1: Innovation, Creativity and Entrepreneurship (ICE); 2: Student In Free Enactus (SIFE) and 3: Entreprenuership and Regenerative Economy Enterprises (ERE). Monsun Industries concentrate on products and professional services commercialization, both locally and globally, to generate profits for FTKW, UMK. Monsun Industries aim to serve as transit platforms for FTKW Student Industrial Training playground and also an Incubator to starts entreprenourial activities after the students graduate. Meanwhile, Monsun Academy focuses on educational and training-related activities that are capable to generate income for local and international markets. Monson Academy will offer diploma couses and coordinate skill certifications to several community colleges, IKBN and DUK which are known as the community of Monsun Valley. Additionally, to strengthen the business and entrepreneurial networking through future advanced information communication technology virtual platforms such as CIN.my, HIN.my and MIN.my will be developed. These virtual platforms are also connected to other recognized international industrial networks around the globe. Therefore, this paper intentionally discusses the future model and entities of FTKW Sustainable Entrepreneurship Ecospehere and how the model can benefit the FTKW-UMK on its human capital development, creative industries and professional branding of the university.